2018
DOI: 10.3389/fmicb.2018.02624
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol (HT) Analogs Act as Potent Antifungals by Direct Disruption of the Fungal Cell Membrane

Abstract: Fungal infections constitute an emerging threat and a prevalent health problem due to increasing number of immunocompromised people and pharmacological or other treatments aiming at viral infections, cancer or allergies. Currently used antifungals suffer from inefficiency, toxic side effects and developing drug-resistance. Additionally, over the last two decades no new classes of antifungals have been approved, emphasizing the urgent need for developing a novel generation of antifungals. Here, we investigate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Regarding the antimicrobial action, the most studied natural compounds are phenolics, although the action of oligopeptides, terpenoids or macrolides have also been reported [ 10 , 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the antimicrobial action, the most studied natural compounds are phenolics, although the action of oligopeptides, terpenoids or macrolides have also been reported [ 10 , 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antifungal activity of a series of chemically synthesized HTyr analogs was investigated. Using Aspergillus nidulans as an in vivo cellular model system, it was shown that antifungal HTyr analogs have an unprecedented efficiency in fungal plasma membrane destruction [93]. It was demonstrated that HTyr has antitrypanosomal and antileishmanial activity [94].…”
Section: Hydroxytyrosolmentioning
confidence: 99%
“…HTyr has been reported to have antiatherogenic, cardioprotective [ 145 , 146 ], anticancer [ 147 , 148 ], neuroprotective [ 149 , 150 ], antimicrobial [ 151 , 152 ], anti-inflammatory, and antiplatelet properties [ 66 , 153 ]. It is released by OLE hydrolysis, which also gives rise to OLE aglycone and elenolic acid [ 154 ].…”
Section: Resultsmentioning
confidence: 99%